Increased concentrations of soluble B7-H3 and interleukin 36 in bronchoalveolar lavage fluid of Children with Mycoplasma pneumoniae pneumonia - Chen, Zhengrong; Zhao, Xin; Zhang, Xinxing; Zhang, Guangbo; Sun, Huiming; Jiang, Wujun; Wang, Yuqing; Zhu, Canhong; Ji, Wei; Yan, Yongdong (BMC infectious diseases, 2016)
Background The purpose of this study is to explore the correlations of interleukin 36 (IL-36) and Soluble B7-H3 (sB7-H3) levels in bronchoalveolar lavage fluid (BALF) with clinical characteristics and laboratory findings. Methods A total of 35 children with M. pneumnoiae pneumonia (MPP) and 15 control subjects were enrolled. BALF concentrations of sB7-H3 and IL-36 were detected using enzyme-linked immunosorbent assays and clinical profiles of children with MPP were obtained. Results Children with MPP had significantly higher levels of sB7-H3 and IL-36 compared to control subjects (both P < 0.05). Meanwhile, children with pleural effusion had significantly higher levels of sB7-H3 and IL-36 compared to children without pleural effusion (both P < 0.05). BALF concentration of sB7-H3 was strongly associated with concentration of IL-36 ( r = 0.796, P < 0.0001) and sB7-H3 was correlated with duration of fever ( r = 0.427, P = 0.11) and length of stay ( r = 0.345, P = 0.043). Both concentrations of sB7-H3 and IL-36 were significantly decreased in convalescent phase after treatment (both P < 0.05). Conclusion Both soluble B7-H3 and IL-36 may play an important role in pathogenesis of M. pneumoniae infection and sB7-H3 could be useful as a prognostic predictor or biomarker of MPP.